“PHONETIC STYLISTIC DEVICES: AN EXPLORATION INTO SOUND AND MEANING” - Abduraxmanova Zilola Yoqubjon qizi; Murodova Fazilat Muxtor qizi ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article provides an in-depth examination of phonetic stylistic devices, which are literary tools that utilize the sound of words to enhance the meaning and emotional impact of language. It discusses the various types of phonetic devices such as alliteration, assonance, consonance, onomatopoeia, rhythm, and meter, and their functions in creating mood, emphasizing themes, and improving memorability. The article also explores the role of these devices across different cultures and literary traditions, their psychological impact, and their evolution in the digital age. Additionally, it addresses their educational importance in teaching language arts and literacy. The conclusion emphasizes the pervasive and enduring influence of phonetic devices in literary expression and communication, reflecting on their importance in human connection and expression.